Achieving High Alignment of Conjugated Polymers by Controlled Dip‐Coating. (13th April 2020) - Li, Qi‐Yi; Yao, Ze‐Fan; Lu, Yang; Zhang, Song; Ahmad, Zachary; Wang, Jie‐Yu; Gu, Xiaodan; Pei, Jian
Abstract: Realizing high polymer chain orientation and ordered thin‐film microstructures is beneficial for efficient charge transport of conjugated polymers. However, achieving a high alignment degree remains a challenge due to the sensitive nature of polymers to the processing conditions. By simply varying concentrations during a dip‐coating method, the component of polymer aggregates that adopt the planar backbones is enlarged and the ensuing assembly process is promoted. Herein, highly oriented polymer thin films of an isoindigo‐based conjugated polymer (PII‐2T) are prepared to enhance polymer orientation resulting in a drastic booming in carrier mobilities of organic field‐effect‐transistors (OFETs). The maximum mobility from aligned polymer films increases by up to 8.3 cm 2 V −1 s −1, which is tenfold beyond the value evaluated from the unaligned direction or traditional spin‐coated samples. The enhanced orientation can also reduce the adverse effects of the contact resistance and facilitate charge transport in transistors. This work demonstrates that the highly aligned conjugated polymer films can be approached by the dip‐coating method while offers a latent cornerstone toward understanding the critical role of processing‐related parameters in determining morphology of solution‐coated thin films. Abstract : Highly ordered thin films of PII‐2T are fabricated to an exceptional alignment degree through a dip‐coating method. A feasible operating window of coating speeds is obtained by tuning coating concentrations. In the transition regime, the coexistence of increasingly high coating speed and short relaxation time give a high alignment degree. The enhanced polymer orientation facilitates the charge transport in transistors.